The Level of Student Satisfaction with the Quality of Universitas Negeri Semarang Postgraduate Program Academic Services - Anggraini, Weni; Wulansari, Endah; Lisdiana, Lisdiana (Universitas Negeri Semarang, 2023)
This study attempted to determine student satisfaction with the quality of Universitas Negeri Semarang (UNNES) Postgraduate Program academic services. It involved 303 Postgraduate Program students chosen using a simple random sampling technique. In terms of methodology, this study used a cross-sectional survey technique. Once the data were obtained, the researchers used descriptive statistics techniques and one-way ANOVA analysis to compare student satisfaction with the quality of UNNES Postgraduate Program academic services in terms of particular ethnography. The research findings show that out of 303 respondents, 71% are at an excellent level of satisfaction, and 22.4% is at a good level of satisfaction, 5% respondents are at a moderate level, 1% are at an alarming level, and 0.7% are at a terrible grade. The services given through SIKADU (UNNES integrated educational system), administrative staff, library, lectures, integrated service unit, workshop and seminars, and telegram gained excellent criterion by the students with a percentage of 71%. Thus, the implementation of services by UNNES Postgraduate Program has been in line with the operational standards and has been able to adapt to the era and needs of the users, particularly the students of UNNES Postgraduate Program.